Verifikasi Keaslian Surat Bunuh Diri Mahira dengan Menggunakan R Stylo - Sinaga, Tantiara Fiesta (Langkawi: Journal of The Association for Arabic and English, 2025)
This study investigates the authenticity of Mahira Dinabila’s suicide note using an exploratory stylometric approach with R Stylo. Mahira, a university student in Indonesia, was found dead in 2023 alongside a letter identified as a suicide note, which was later questioned by her family due to inconsistencies in linguistic style and handwriting. While initial forensic examination focused solely on graphological analysis, this research aims to explore the linguistic characteristics of the letter to determine whether it aligns with authentic suicide note patterns. Using a corpus of 20 verified suicide notes from Indonesian university students, this study applies computational stylometry via R Stylo, focusing on MFW, z-score normalization, and Classic Delta distance measures. Findings reveal that Mahira’s suicide note lacks emotional elements typically present in genuine suicide notes. Instead, the note is highly structured and dominated by time markers, suggesting narrative planning rather than emotional spontaneity. The contrast between Mahira’s suicide note and the reference corpus underscores the value of stylometric features in distinguishing textual authenticity. This study contributes to forensic linguistics through computational stylometry by demonstrating how linguistic features can provide measurable indicators for verifying the authenticity of emotionally charged personal documents, particularly in contexts where conventional forensic methods may fall short.